👤
Pisialy83
a fost răspuns

Descompuneți în factori (2x+1)^2-9
la sfarsir da 4(x-1)(x+2), cum? va rog trebuie acum ofer 55 puncte​


Răspuns :

Formulă :

[tex] {a}^{2} - {b}^{2} = (a - b)(a + b)[/tex]

[tex] {(2x + 1)}^{2} - 9 = {(2x + 1)}^{2} - {3}^{2} [/tex]

[tex]a = 2x + 1[/tex]

[tex]b = 3[/tex]

[tex] = (2x + 1 - 3)(2x + 1 + 3)[/tex]

[tex] = (2x - 2)(2x + 4)[/tex]

[tex] = 2(x - 1) \times 2(x + 2)[/tex]

[tex] = 2 \times 2(x - 1)(x + 2)[/tex]

[tex] = 4(x - 1)(x + 2)[/tex]

(2x + 1)² - 9 =

Folosim a² - b² = (a + b)(a - b)

= (2x + 1)² - 3²

= (2x + 1 + 3)(2x + 1 - 3)

= (2x + 4)(2x - 2)

= 2(x + 2)·2(x - 1)

= 4(x + 2)(x - 1)